Disclosing HIV diagnosis to children in Odi district, South Africa: Reasons for disclosure and non-disclosure - Johanna M. Mahloko; Sphiwe E. Madiba (AOSIS, 2012)
Background: The increasing access to antiretroviral therapy (ART) and survival of HIV- infected children has posed challenges to caregivers on disclosing the HIV diagnosis to children. Objectives: The objectives of this study was to determine the reasons of caregivers for the disclosure and non-disclosure of the HIV diagnosis to children on ART and to determine the caregivers' perceptions of children's reaction to disclosure. Method: A cross-sectional study was conducted amongst 149 caregivers of children between 4-17 years who receive ART from a district hospital in South Africa. Descriptive and inferential statistics were used in the analysis of data. Results: The prevalence of disclosure was 40% and the mean age of disclosure was 9.3 years. Reasons for disclosure included that the child was not adhering to treatment (n = 59; 39%); the child was consistently asking questions about the treatment and nature of the disease (n = 59; 39%). Reasons for non-disclosure were that the child was too young (n = 90; 72%); the child would tell others about diagnosis (n = 90; 21.1%); the child would be socially rejected (n = 90; 18.6%); fear of negative consequences for the child (n = 90; 13.3%); and caregivers do not know how to tell or approach disclosure (n = 90; 8.9%). Conclusion: Caregivers disclosed the diagnosis so that their child would adhere to ART medication; non-disclosing caregivers delayed disclosure because their children were too young to understand the HIV diagnosis. Disclosure of HIV to children should be integrated into regular discussions with caregivers of children in ART settings to improve their knowledge and skills to manage disclosure.